Exploring ICQs as a tool for effective English language teaching: A systematic literature review - Khairunnisa, Ulfah; Maulina; Rahmiatin, Titin; Nurfaidah, Sitti; Sain, Yuliyanah; Halim, Abdul; Osabel, Arnie C.; Villaflor, Mark Ren D. (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This systematic literature review examines empirical studies on ICQ in EFL classrooms. Guided by PRISMA 2020, eleven peer-reviewed articles published between 2016 and 2025 were selected from Google Scholar, Taylor & Francis Online, and ERIC. The review identifies ICQ types, methodological trends, and pedagogical contributions to instruction-giving and understanding-check practices. Findings indicate that ICQs are mainly used as comprehension checks, confirmation checks, and clarification requests. Form-based ICQs commonly appear as yes/no and Wh-questions, while display questions dominate the purpose-based category. Methodologically, qualitative studies dominated, followed by mixed-methods and limited quantitative research. The review concludes that effective ICQs should be specific, task-based, and evidence-seeking to strengthen instructional clarity and classroom interaction in EFL contexts.